Q fever vaccination of children in Australia: Limited experience to date. (2nd January 2019) - Armstrong, Mark; Francis, Josh; Robson, Jenny; Graves, Stephen; Mills, Deborah; Ferguson, John; Nourse, Clare
Abstract : Aim: Q fever is a zoonotic disease caused by the bacterium Coxiella burnetii and is associated with significant morbidity and mortality in both adults and children. Australia is the only country that has produced and registered a Q fever vaccine for human use, but this vaccine is licenced only for people aged over 15 years as data and experience in children are limited. This review describes the experience of Q fever vaccination of known paediatric cases in Australia to date. Methods: Patients aged younger than 15 years who received the Q fever vaccination had data abstracted from medical records after consent was obtained from the relevant guardians. Data on risk factors for Q fever, skin testing procedure, dose of vaccination, adverse effects and follow‐up assessment were obtained. Results: Twelve children were identified as having received the Q fever vaccination. Vaccination was feasible, with empirical weight‐based dose adjustment performed for younger children. There were no significant adverse effects. Conclusions: Q fever vaccine may be safe in children and should be considered in children who are at significant risk of Q fever infection. Safe vaccine protocols with proven efficacy will allow children of all ages to be protected. Prospective studies of vaccination in children are indicated. Expanding available Q fever registries to include children would allow outcomes to be systematically followed.